A Comparison of Product Weight Method and Simple Addition Weight Method in Employee Selection System - Alwani, Adie G.; Avianto, Donny (International Journal Software Engineering and Computer Science (IJSECS), 2023)
Tegar Mandiri Steam Ironing Service is a business operating in the steam ironing service industry, located in the Boyolali area, specifically in Dlingo Village, Mojosongo Subdistrict, Boyolali Regency, Central Java. "Tegar Mandiri" still employs conventional methods in the selection and recruitment of employees without leveraging technology. Although the implementation of conventional employee recruitment has been smooth, several issues have arisen. For instance, prospective applicants must visit in person to find out about job vacancies. Furthermore, the registration process for potential employees is still manually executed, requiring individuals to physically visit the site. Consequently, the administrative staff must record each applicant's details individually, leading to an ineffective data collection process and vulnerability to data loss or damage in physical records. The implementation phase was conducted through coding in PHP, adopting the Simple Additive Weighting (SAW) and Weight Product (WP) methods. Although both methods exhibit minor differences in their comparison, the results tend to favor the SAW method. The accuracy level of the SAW method reaches 96% as it has advantages over the WP method in terms of data normalization. The SAW method can address issues related to scale and unit differences among various criteria. Therefore, the SAW method is more accurate and dominant in determining the priority of employee recruitment